Optimization of trigeneration systems by Mathematical Programming: Influence of plant scheme and boundary conditions. (1st November 2015) - Piacentino, A.; Gallea, R.; Cardona, F.; Lo Brano, V.; Ciulla, G.; Catrini, P.
Highlights: Lay-out, design and operation of trigeneration plant is optimized for hotel building. The temporal basis used for the optimization is properly selected. The influence of plant scheme on the optimal results is discussed. Sensitivity analysis is performed for different levels of tax exemption on fuel. Dynamic behavior of the cogeneration unit influences its optimal operation strategy. Abstract: The large potential for energy saving by cogeneration and trigeneration in the building sector is scarcely exploited due to a number of obstacles in making the investments attractive. The analyst often encounters difficulties in identifying optimal design and operation strategies, since a number of factors, either endogenous (i.e. related with the energy load profiles) and exogenous (i.e. related with external conditions like energy prices and support mechanisms), influence the economic viability. In this paper a decision tool is adopted, which represents an upgrade of a software analyzed in previous papers; the tool simultaneously optimizes the plant lay-out, the sizes of the main components and their operation strategy. For a specific building in the hotel sector, a preliminary analysis is performed to identify the most promising plant configuration, in terms of type of cogeneration unit (either microturbine or diesel oil/natural gas-fueled reciprocate engine) and absorption chiller. Then, sensitivity analyses are carried out to investigate the effects induced by: (a) tax exemption for the fuel consumed in "efficient cogeneration" mode, (b) dynamic behavior of the prime mover and consequent capability to rapidly adjust its load level to follow the energy loads.